Endocannabinoid System Unlocks the Puzzle of Autism Treatment via Microglia - Su, Tangfeng; Yan, Yu; Li, Qiang; Ye, Jiacai; Pei, Lei (Frontiers in Psychiatry, 2021)
Autism spectrum disorder (ASD) is a serious neurodevelopmental disorder and characterized by early childhood-onset impairments in social interaction and communication, restricted and repetitive patterns of behavior or interests. So far there is no effective treatment for ASD, and the pathogenesis of ASD remains unclear. Genetic and epigenetic factors have been considered to be the main cause of ASD. It is known that endocannabinoid and its receptors are widely distributed in the central nervous system, and provide a positive and irreversible change toward a more physiological neurodevelopment. Recently, the endocannabinoid system (ECS) has been found to participate in the regulation of social reward behavior, which has attracted considerable attention from neuroscientists and neurologists. Both animal models and clinical studies have shown that the ECS is a potential target for the treatment of autism, but the mechanism is still unknown. In the brain, microglia express a complete ECS signaling system. Studies also have shown that modulating ECS signaling can regulate the functions of microglia. By comprehensively reviewing previous studies and combining with our recent work, this review addresses the effects of targeting ECS on microglia, and how this can contribute to maintain the homeostasis of the central nervous system, and thus improve the symptoms of autism. This will provide insights for revealing the mechanism and developing new treatment strategies for autism.